EFEKTIVITAS PEMBINAAN MUTU SUMBER DAYA MANUSIA (Studi Kasus di MTs. Hidayatul Falah Nagrak Sukabumi) - Badriya Hisniati, Sally; Hariyanto, Teguh; Hidayatul Ummah, Nida; Solihin, Dadin (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
This approach uses a qualitative research approach based on the philosophy of post-positivism, used to examine the natural condition of objects, researchers as key instruments, data source sampling is done purposively and snowball. Collection techniques with triangulation (combined), data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. This research in the form of field research is researchers conduct direct research on objects studied and conducted data collection found in the field. Empiric data related to the effectiveness of human resource quality development (HR) in MTs. Hidayatul Falah refers to descriptive qualitative attachment. The results showed that the effectiveness of HR quality development in MTs. Hidayatul Falah is a planned program in the development of HR quality is done well. The planned program in hr quality development includes planning, employee acceptance, training in the form of In House training, workshops, academic level improvement, work motivation, providing incentive and performance compensation, improving discipline, development through promos, rotation, and mutation. Organizing the quality of Human Resources development is done well such as doing placement, division of tasks, and assignment of each employee coupled with supervision. The implementation of HR quality development is carried out according to planning and is carried out by all units with adjusted budgets. Evaluation of HR quality development is carried out through school self-evaluation activities, supervision, and teacher assessment activities. Supporting factors in the development of HR quality are the leadership of the principal and the cooperation of each unit. While the inhibiting factor is that there is still a lack of comments and employee awareness. The effectiveness of the development program on the quality of human resources is increasing the performance of the academic, increasing the responsibility of employees in completing tasks well, learners learning well, activities have been programmed, and increasing the discipline of teachers and learners. Pendekatan dalam penelitian ini menggunakan pendekatan penelitian secara kualitatif yakni penelitian yang berlandaskan pada filsafat post positivisme, digunakan untuk meneliti pada kondisi objek yang alamiah, peneliti sebagai instrumen kunci, pengambilan sampel sumber data dilakukan secara purposive dan snowball. Teknik pengumpulan dengan trianggulasi (gabungan), analisis data bersifat induktif/kualitatif serta hasil penelitian kualitatif lebih menekankan makna daripada generalisasi. Penelitian ini berupa field research yaitu peneliti mengadakan penelitian langsung terhadap objek yang diteliti dan dilakukan pengumpulan data yang ditemukan di lapangan. Data empiric yang berhubungan dengan efektivitas pembinaan mutu sumber daya manusia (SDM) di MTs. Hidayatul Falah hal ini merujuk pada pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa efektivitas pembinaan mutu SDM di MTs. Hidayatul Falah yaitu penyusunan program yang direncanakan dalam pembinaan mutu SDM dilakukan dengan baik. Program yang direncanakan dalam pembinaan mutu SDM tersebut meliputi perencanaan, penerimaan pegawai, pelatihan berupa In House Traning, workshop, peningkatan jenjang akademik, motivasi kerja, memberikan insentif dan kompensasi kinerja, peningkatan kedisiplinan, pengembangan melalui promosi, rotasi, dan mutasi. Pengorganisasian pembinaan mutu SDM dilakukan dengan baik seperti melakukan penempatan, pembagian tugas, dan tupoksi masing-masing pegawai dibarengi dengan pengawasan. Pelaksanaan pembinaan mutu SDM dilakukan sesuai perencanaan, dan dilaksanakan oleh semua unit dengan anggaran disesuaikan. Evaluasi pembinaan mutu SDM dilakukan melalui kegiatan evaluasi diri sekolah, supervise, dan kegiatan penilaian kinerja guru. Faktor penunjang dalam pembinaan mutu SDM yaitu kepemimpinan kepala sekolah, dan kerjasama setiap unit. Sedangkan faktor penghambat yaitu masih terdapat minimnya kompentesi dan kesadaran pegawai. Efektivitas program pembinaan terhadap mutu SDM yaitu meningkatnya prestasi akedemik, meningkatnya tanggungjawab pegawai dalam menyelesaikan tugas dengan baik, peserta didik belajar dengan baik, kegiatan sudah terprogram, serta meningkatnya kedisiplinan guru dan peserta didik.